2001
DOI: 10.1109/78.928691
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic analysis of the LMS algorithm with a saturation nonlinearity following the adaptive filter output

Abstract: This paper presents a statistical analysis of the least mean square (LMS) algorithm with a zero-memory scaled error function nonlinearity following the adaptive filter output. This structure models saturation effects in active noise and active vibration control systems when the acoustic transducers are driven by large amplitude signals. The problem is first defined as a nonlinear signal estimation problem and the mean-square error (MSE) performance surface is studied. Analytical expressions are obtained for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 17 publications
1
42
0
3
Order By: Relevance
“…The results obtained in [5] agreed with the observations of several authors in ANC area [2][3][4]6]. The possibility of quantifying the nonlinear effects on the performance surface motivated the search for new algorithms that could be capable of overcoming the poor steady-state performance of the LMS algorithm in a nonlinear environment.…”
Section: I Introductionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results obtained in [5] agreed with the observations of several authors in ANC area [2][3][4]6]. The possibility of quantifying the nonlinear effects on the performance surface motivated the search for new algorithms that could be capable of overcoming the poor steady-state performance of the LMS algorithm in a nonlinear environment.…”
Section: I Introductionsupporting
confidence: 93%
“…A recent work [5] studied the behavior of the LMS algorithm subjected to a nonlinear influence at the adaptive filter output. It was demonstrated that the mean converged weights corres pond to a biased solution with respect to the minimum of the MSE surface.…”
Section: I Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…nn This approximation has been successfully applied in References [4,5]. In this section, we show that the MOV-FXLMS algorithm leads to a biased steady-state mean weight solution.…”
Section: The Mean Weight Behaviour In a Non-linear Environment}analysismentioning
confidence: 99%